Biallelic, Selectable, Knock-in Targeting of CCR5 via CRISPR-Cas9 Mediated Homology Directed Repair Inhibits HIV-1 Replication - Scheller, Stefan H.; Rashad, Yasmine; Saleh, Fayez M.; Willingham, Kurtis A.; Reilich, Antonia; Lin, Dong; Izadpanah, Reza; Alt, Eckhard U.; Braun, Stephen E. (Frontiers in Immunology, 2022)
Transplanting HIV-1 positive patients with hematopoietic stem cells homozygous for a 32 bp deletion in the chemokine receptor type 5 (CCR5) gene resulted in a loss of detectable HIV-1, suggesting genetically disrupting CCR5 is a promising approach for HIV-1 cure. Targeting the CCR5-locus with CRISPR-Cas9 was shown to decrease the amount of CCR5 expression and HIV-1 susceptibility in vitro as well as in vivo. Still, only the individuals homozygous for the CCR5-Δ32 frameshift mutation confer complete resistance to HIV-1 infection. In this study we introduce a mechanism to target CCR5 and efficiently select for cells with biallelic frameshift insertion, using CRISPR-Cas9 mediated homology directed repair (HDR). We hypothesized that cells harboring two different selectable markers (double positive), each in one allele of the CCR5 locus, would carry a frameshift mutation in both alleles, lack CCR5 expression and resist HIV-1 infection. Inducing double-stranded breaks (DSB) via CRISPR-Cas9 leads to HDR and integration of a donor plasmid. Double-positive cells were selected via fluorescence-activated cell sorting (FACS), and CCR5 was analyzed genetically, phenotypically, and functionally. Targeted and selected populations showed a very high frequency of mutations and a drastic reduction in CCR5 surface expression. Most importantly, double-positive cells displayed potent inhibition to HIV-1 infection. Taken together, we show that targeting cells via CRISPR-Cas9 mediated HDR enables efficient selection of mutant cells that are deficient for CCR5 and highly resistant to HIV-1 infection.